2008
DOI: 10.1111/j.1467-8683.2008.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Corporate Social Responsibility Synergies and Interrelationships

Abstract: Manuscript Type: Empirical Research Questions/Issue: This paper seeks to explore the interrelationships between corporate governance (CG) and corporate social responsibility (CSR): first, theoretically, by reviewing the literature and surveying various postulations on offer; second, empirically, by investigating the conception and interpretation of this relationship in the context of a sample of firms operating in Lebanon. Accordingly, the paper seeks to highlight the increasing cross-connects or interfaces be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
546
1
47

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 636 publications
(619 citation statements)
references
References 58 publications
25
546
1
47
Order By: Relevance
“…The process-oriented standards are applied in particular industries. While other performance-oriented standards are more generic in their approach as they focus on specific areas such as human rights, labour standards, environmental protection and the like (see Jamali, Safieddine, & Rabbath, 2008). Camilleri (2012) provides some examples of the most popular standards and reporting instruments in a global context.…”
Section: The Csr Languagementioning
confidence: 99%
“…The process-oriented standards are applied in particular industries. While other performance-oriented standards are more generic in their approach as they focus on specific areas such as human rights, labour standards, environmental protection and the like (see Jamali, Safieddine, & Rabbath, 2008). Camilleri (2012) provides some examples of the most popular standards and reporting instruments in a global context.…”
Section: The Csr Languagementioning
confidence: 99%
“…But the implication of religion on economic policies such as corporate governance cannot be isolated. While religious principles can trigger good corporate governance (Jamali et al, 2008), our data suggests otherwise. E2 notes that:…”
Section: C1 Added Thatmentioning
confidence: 82%
“…In contrast, Sommer et al (2013) and Aldohni (2014) demonstrate that religion can undermine responsible corporate behaviour. Another strand of literature (Jamali et al, 2008;Hilary & Hui, 2009;El Ghoul et al, 2012) indicated that the relationship between religion and corporate governance is context-dependent. For instance, Kuran (2009) and Norris and Inglehart (2011) expressed that in less-religious countries, the relationship between religion and corporate governance is weak.…”
Section: Practical Implications Of Study and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between stakeholder theory and environmental and social reporting is given attention within the accounting literature (Donaldson and Preston, 1995;Jamali et al, 2008) depicting the theory in two branches -normative/ ethical and managerial/ instrumental branch as per Mahadeo et al (2011). The ethical branch focuses on the responsibility of a company "to account for its actions", while the managerial branch concentrate around "the need to control stakeholders who are deemed to have a more direct and critical impact on the company" as per Mitchell, Agle and Wood, 1997;Roberts, 1992;Ullman, 1985in Mahadeo et al (2011.…”
Section: Introductionmentioning
confidence: 99%